Anterior maxillary teeth crown lenghtening and indirect veneer for esthetics rehabilitation: A case report - Ganiezha Cindananti; Nina Dhaniar; Nurshiffa Hanifatul Amrina Jaelani; Cathelea Raihan Avicenna; Widya Saraswati (Conservative Dentistry Journal, 2022)
Background: Crown Lengthening is a surgical procedure performed to create a symmetrical gingival line and is carried out to expose necessary additional tooth structure. A short clinical crown occurs as a result of dental malformations, eruption disharmony, and genetic variation. Purpose: The purpose of this case report is to explain the treatment management of Crown Lengthening over the case of diastema closure by indirect veneer restoration. Case: 32 years old female presented with a chief complaint over a space between her anterior maxillary teeth. She wants to rectify her smile. Case Management: The management in this case are preparation of Digital Smile Design (DSD), Crown Lengthening on 11 and 21, and Indirect Veneer on 11, 21, 22. Conclusion: Aesthetical rehabilitation could be attained by an indirect veneer treatment followed by a gingival management which is Crown Lengthening.